The scale‐up of a tissue engineered porous hydroxyapatite polymer composite scaffold for use in bone repair: An ovine femoral condyle defect study. Issue 4 (23rd July 2014) - Tayton, Edward; Purcell, Matthew; Smith, James O.; Lanham, Stuart; Howdle, Steven M.; Shakesheff, Kevin M.; Goodship, Allen; Blunn, Gordon; Fowler, Darren; Dunlop, Douglas G.; Oreffo, Richard O. C
Abstract The development of an osteogenic bone graft substitute has important practical and cost implications in many branches of medicine where bone regeneration is required. Previous in vitro and small animal (murine) in vivo studies highlighted a porous hydroxyapatite/poly (dl‐lactic acid) composite scaffold in combination with skeletal stem cells (SSCs) as a potential bone graft substitute candidate. The aim of the current study was to scale up the bone cell‐scaffold construct to large animals and examine the potential for repair of a critical‐sized defect via an ovine model. SSC seeded scaffolds (and unseeded scaffold controls) were implanted bilaterally into ovine femoral condyle critical defects for 3 months. A parallel in vitro analysis of ovine SSC seeded scaffolds was also performed. Post mortem mechanical indentation testing showed the bone strengths of the defect sites were 20% (controls) and 11% (SSC seeded scaffolds) those of normal cancellous bone (p < 0.01). MicroCT analysis demonstrated new bone formation within all defects with a mean increase of 13.4% in the control scaffolds over the SSC seeded scaffolds (p = 0.14). Histological examination confirmed these findings, with enhanced quality new bone within the control defects. This study highlights important issues and steps to overcome in scale‐up and translation of tissue engineered products. The scaffold demonstrated encouraging results as an osteoconductive matrix; however, further work is required with cellular protocols before any human trials. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1346–1356, 2015.